Dietary Intake Pattern and Nutritional Status of Women of Reproductive Age in Slum Areas of Pokhara Metropolitan - Babita Kandel; Dhurba Khatri; Arun Kumar Koirala; Yamuna Chhetri; Alisha Manandhar (Journal of Nutrition and Metabolism)
Introduction. The pattern of diet intake is associated with food availability and the intake of nutrients from different food groups and is an important component of nutritional status. The dietary habits of individuals are integral to understanding their nutritional wellbeing, making this assessment crucial for public health interventions. The objective of the study was to assess the dietary intake pattern and nutritional status among women of reproductive age in slum areas of Pokhara Metropolitan. Methodology. A cross-sectional analytical study was conducted to assess the dietary intake pattern and nutritional status among 404 women of reproductive age in the slum area of Pokhara from June 2019 to December 2019. A simple random sampling technique was used to select the wards while a purposive sampling technique was used to collect the samples. 24-hour recall meal-based questions and anthropometric measurements were used for collecting data. Data were entered into EpiData and analyzed using SPSS version 16 software for analysis. Frequency and mean, median, chi-square test, and logistic regression were performed. Results. The mean (±SD) age (SD) of the participants was 31 (±9.25) years, and most of the participants belonged to the age group 25–35 years. Out of 404 women of reproductive age, 99% of the participants consumed starchy staple foods daily, while 56.7% ate vegetables daily, and nearly half frequently consumed prepackaged foods and soft drinks. Among the total participants, 41.3% were found with a normal BMI, 37.6% were overweight, and only 12.4% were underweight. There was a significant association between underweight and age, women’s occupation, and frequency of food consumption per day. Age, knowledge of nutrition, and frequency of food consumption per day were found to be associated factors with being overweight at a p value <0.05. Conclusion. Age, occupation status, and frequency of food consumption were the key predictors of being underweight, and age, knowledge regarding nutrition, and frequency of meals were the key predictors of being overweight. Developing countries must emphasize the importance of considering these factors in public health interventions and strategies aimed at promoting healthy weight management. More studies are needed.